دراسة تباين نسبة بعض الخصائص الإنتاجية، ومحتوى الزيت العطري تبعاً لاختلاف زمن الحش للزعتر الشائع Thymus vulgaris L. المزروع في بانياس من الساحل السوري (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2016)
يهدف البحث إلى دراسة تأثير خمسة مواعيد حش (النمو الخضري, وبداية تفتح النورات الزهرية, وبداية الإزهار, والإزهار الكامل, واكتمال النمو الخضري في بداية شهر أيلول، وذلك للنباتات التي سبق حشها), على بعض المؤشرات المورفولوجية والإنتاجية لنبات الزعتر الشائع Thymus vulgaris L.. صممت التجربة بطريقة العشوائية الكاملة في ثلاثة مكررات. تم استخدام تحليل التباين Anova باستخدام برنامج Genestat لحساب أقل فرق معنوي LSD عند مستوى المعنوية 5%. أظهرت النتائج تفوق موعد الحش الخامس معنوياً على باقي المواعيد من حيث مؤشر عدد الفروع (16.50 فرع / نبات), والإنتاجية من الوزن الرطب (55.00 غ / نبات), والإنتاجية من المادة الجافة (27.08 غ / نبات), بينما تفوق موعد الحش الثاني معنوياً على باقي المواعيد من حيث النسبة المئوية للزيت العطري (حجم / وزن) (2.10%), كما بلغ النبات أعلى ارتفاع له عند موعد الحش الرابع (21.50 سم). وهذه النتائج توضح أهمية تحديد موعد الحش، لارتباط نسبة الزيت، وكل من الوزن الجاف، والوزن الرطب به.The research aims to study the effect of five harvesting wed (vegetative growth, the beginning of open inflorescences flowering, the beginning of flowering, full bloom, and completeness of the vegetative growth at the beginning of the month of September and that of plants that have already cutted), some of the morphological and productivity indicators for common thyme Thymus vulgaris L . Experiment was designed by the complete randomized manner in three replicates. Statistical analysis was performed by Anova test using Genestat and account teams less moral LSD at a significance level of 5%. Results showed superiority date mower fifth morally on the rest of the dates in terms of index number of branches (16.50 branch / plant), productivity of the wet weight (55.00 g / plant), productivity of dry matter (27.08 g / plant), while the superiority of the date of the second mowing morally the rest of the appointments in terms of the percentage of essential oils (size / weight) (2.10%), also reached the top of the plant at the time of his high mowing fourth (21.50 cm). Highlights the importance of the results by identifying the optimal harvesting date to get the most fresh and dry weight of material and the highest percentage of essential oil, and the resulting economic return to the farmer healthy and beneficial to the consumer, with the continued preservation of the existence of the plant and its tender.